PENGARUH RETURN ON ASSET (ROA), DEBT TO TOTAL ASSET (DTA) DAN TOTAL ASSET TURNOVER (TATO) TERHADAP RETURN SAHAM PADA PERUSAHAAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2014 - Hilmi Abdullah; Soedjatmiko - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, This research empirically test and prove whether ROA, DTA and TATO effect on stock return on a property company listed on the Indonesia Stock Exchange (BEI) in 2011-2014. The method used in this research is quantitative descriptive. Tools statistical tests used in this study were multiple linear regression through the program Stats Product and Service Solution (SPSS 16). The population in this research is a property company that is listed on the Stock Exchange Period 2011-2014 amounted to 49 companies. Samples in this study amounted to 31 companies selected by using purposive sampling technique. The data used in this research is financial statements and stock prices is through the 2011-2014 period www.idx.co.id sites; www.finance.yahoo.com and www.sahamok.com. The test results simultaneously stated that ROA, DTA and TATO has no effect on stock returns as evidenced by the F-count equal to 1.331 and the probability of 0.286. Partial test showed that ROA has no effect on stock returns is by t-test amounted to 1.437 and the probability of 0.163. DTA has no effect on stock returns is by t-test amounted to 0.223 and the probability of 0.825 and TATO has no effect on stock returns is by t-test amounted to 0.152 and the probability of 0.880. The conclusion of this study property company's financial statements have no effect on stock returns for the value of R square (R2) is only 13.3%.